Meliotropic wellbeing mindset: a catalyst for sustaining long-term wellbeing - Burke, Jolanta; Giraldez-Hayes, Andrea; Dunne, Padraic James (Frontiers in Psychology, 2025)
Positive psychology has contributed significantly to wellbeing, primarily through Positive Psychology Interventions (PPIs). However, most research in PPIs has focused on their impact on positive outcomes rather than the conundrum of real-life application. This qualitative study explored how 22 alumni of positive psychology programmes integrated their wellbeing knowledge into daily life to sustain their wellbeing over time. Participants reported a shift from using structured PPIs for enhancing their wellbeing to a new mindset that supported their long-term wellbeing. Specifically, five themes have emerged from the data, which represented manifestations of their changed mindset: (1) intentional living, (2) wellbeing hygiene, (3) self-acceptance, (4) embodiment, and (5) environmental awareness. These themes describe “Meliotropic Wellbeing Mindset,” which is an intrinsically motivated, wholly approach to living a good life that integrates wellbeing into everyday practice through planned or spontaneous, context-sensitive, and identity-aligned practices. These findings challenge the field’s focus on PPIs and suggest that sustainable wellbeing is more about developing mindsets that orient individuals toward continual improvement than practising PPIs. Deriving from the Latin “melior” (better) and Greek “tropism” (movement toward), Meliotropism describes a tendency to actively align thoughts, behavior, attitudes, and life choices with what makes life worth living, even amid adversity. This research highlights the importance of fostering Meliotropic Wellbeing Mindset in real-world contexts, where wellbeing is an ongoing, self-directed, and contextually responsive process.